(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The text provides information about medicinal plants used in the treatment of heart diseases, their morphology, and methods of preparing infusions from them. Key words: medicinal lemon balm, medicinal valerian, common hawthorn, motherwort, hypotensive, spasmolytic, hypertension, hypotension, cardiac activity. Medicinal lemon balm - Melissa officinalis Lamiaceae. Plant description: Medicinal lemon balm belongs to the Lamiaceae family, it is a fragrant plant with a lemon scent, a perennial herb covered with many years of downy hair. The stem is sturdy, square, reaches a height of up to 120 cm. The leaves are opposite, serrated, with a length of up to 4 cm. The fruit is a three-seeded nutlet. The plant begins vegetative growth in early spring. It blooms in June to August. Medicinal lemon balm grows in shrubs, forests, and along riverbanks. Usage: The plant is harvested during the flowering period when the flowers are fully open. Lemon balm has soothing properties. Infusions of lemon balm are used as a cardiac tonic, diuretic, antipyretic, and analgesic. According to Ibn Sina, the plant "strengthens the heart, invigorates, aids in digestion, and provides assistance when hiccups occur." The analysis is based on global scientific views published in the International Scientific Journal 2023 Vol1 Issue 4 IF (Impact Factor) 8.2 / 2023, which can be found at https://academics.uz/index.php/awsit. (https://academics.uz/index.php/awsit) Lemon balm’s green leaves, when applied as a poultice to areas where blood circulation is frequently disturbed, help improve blood circulation. Uzbek Medicinal valerian - Valeriana officinalis.